EXISTENCE OF GENERAL COURSES: A STUDY OF ACEHNESE HISTORY AND CULTURE AS A COMPULSORY SUBJECT AT SAMUDRA UNIVERSITY - Usman, Usman; Akob, Bachtiar; Rahmatsyah, Rahmatsyah; Asnawi, Asnawi; Bukhari, Bukhari; Zulfiani, Zulfiani (Universitas Negeri Medan, 2023)
In the vision and mission of Samudra University